Repair of Primary Bilateral cleft Lip - Puthucode V Narayanan (Wolters Kluwer Medknow Publications, 2022)
Bilateral cleft lips have traditionally been a challenge to repair and the results have not been very favorable. However, advances in the recent past in the understanding of the nature of the deformity, especially the nasal component have brought a revolutionary change in the approach to these patients, with remarkable improvement in the outcome. The management of the premaxilla and its alignment with the maxillary shelves presurgically is crucial for the optimal treatment of such patients. The treatment protocol and technique followed at our center are described. It is a modification of the Mulliken technique. The philtrum is designed to be small in keeping with its rapid growth potential. The philtral flap is raised and the orbicularis oris muscles from the two sides are mobilized and brought together in the mid-line. Adequate mobilization of the muscles is necessary to avoid closure under tension. The evolution of the concept of primary rhinoplasty is described. The technique of preschool columellar lengthening and open rhinoplasty that is followed at our center is described. Unfavorable results include scarring, dehiscence, and central vermillion deficiency.